Antibacterial and Antibiofilm Activity of Amoxicillin and Citrus sinensis Extract Against A. actinomycetemcomitans: Antibacterial and Antibiofilm Activity of Amoxicillin and Citrus sinensis - Alexander Jonathan Nyomanto; Priska Natassya; Sheila Soesanto (Universitas Syiah Kuala, 2025)
Aggregatibacter actinomycetemcomitans is a major bacterial pathogen causing localized aggressive periodontitis, where its ability to form biofilms increases resistance to antibiotic therapies. Amoxicillin is commonly used as a treatment; however, prolonged use may lead to bacterial resistance. Alternative natural treatments with antibacterial and antibiofilm activities, such as the ethanol extract of Citrus sinensis peel, which is rich in flavonoids and saponins with bioactive potential, are needed. To investigate the antibacterial and antibiofilm effects of combining amoxicillin with the ethanol extract of C. sinensis peel against A. actinomycetemcomitans. This laboratory study was conducted in vitro using a post-test-only control-group design. Antibacterial testing was carried out using the plate count method, and antibiofilm testing was performed using the microtiter plate biofilm assay. The tested samples included amoxicillin (½ MBC) combined with the ethanol extract of C. sinensis peel at concentrations of 100%, 50%, 25%, 12.5%, 6.25%, and 3.125%, along with aquadest as the negative control and amoxicillin as the positive control. All concentrations of C. sinensis peel extract exhibited antibacterial effects against A. actinomycetemcomitans. The antibiofilm effect against A. actinomycetemcomitans was observed at 1 and 3 hours for extract concentrations of 3.125%, 6.25%, and 12.5%, with the 100% extract group demonstrating significant antibiofilm activity at all incubation times (1, 3, and 24 hours). At 24 hours, during the biofilm maturation phase, biofilms were less resistant, with antibiofilm effects observed at extract concentrations of 3.125%, 6.25%, and 12.5%, as well as in the 100% extract group. Conclusion: The combination of amoxicillin and the ethanol extract of C. sinensis peel has antibacterial and antibiofilm effects against A. actinomycetemcomitans